(untitled) (Orfeu, 2016)
This paper shows an analytical proposal of the sonorities built by the rock Brazilian band “O Terço”, during the 70’s. It is shown that the group, in question, did not bring the fixed idea of music, or rather, of Brazilian rock. With a diversity of influences from the rock style to several sonorities already considered part of the Brazilian music, “O Terço’s” music brought their country and urban interpretation, tradition and modernity, praise to rock and criticism towards the Brazilian civil-military dictatorship scene. Such ideas will be analyzed through some songs selected for this study. To this end, it is proposed to conjugate the methodological tools from the authors Bruce Baugh (1994), Marcos Napolitano (2002), Felipe Trotta (2008) and Paul Friedlander (2012), showing how the musical elements establish a dynamic game with their historical time. It has also been discussed some theories and identity issues through Fredrik Barth (1998), Stuart Hall (1998) and Miguel Alberto Bartolomé (2006). With these, it is pointed that the identity is always built within the context, therefore, it is relational.